Case report: Stereotactic MR-guided adaptive radiotherapy for inoperable urothelial carcinoma at the renal pelvis - Thaweerat, Wajana; Dankulchai, Pittaya (Frontiers in Oncology, 2024)
We report the case of an 87-year-old female with upper tract urothelial carcinoma at left renal pelvis. She received stereotactic body radiotherapy of 35 Gy in 5 fractions for palliative treatment of hematuria which was delivered by a 1.5 T magnetic resonance (MR) imaging guided linear accelerator. Her symptom was relieved after treatment and post-treatment imaging revealed a complete response of the primary tumor. Thus, this case showed that stereotactic MR-guided radiotherapy could be an appealing option for inoperable patients although radiotherapy is infrequently mentioned in the current treatment guideline of upper tract urothelial carcinoma. Daily adaptive planning from MR images obtained before treatment could result improve the target dose and minimize organs at risk dose. This may lead to a decrease in radiation adverse effects including worsening renal function due to the renal pelvis tumor's proximity to the kidney.